Effects of hedgerow systems on soil moisture and unsaturated hydraulics conductivity measured by the Libardi method - S Prijono; M T S Laksmana; D Suprayogo (Brawijaya University, 2016)
The hedgerow systems are the agroforestry practices suggesting any positive impacts and negative impacts on soil characteristics. This study evaluated the effects of hedgerows on the unsaturated hydraulic conductivity of soil with the Libardi method approach. This study was conducted in North Lampung for 3 months on the hedgerow plots of Peltophorum dassyrachis (P), Gliricidia sepium (G), and without hedgerow plot (K), with four replications. Each plot was watered as much as 150 liters of water until saturated, then the soil surface were covered with the plastic film. Observation of soil moisture content was done to a depth of 70 cm by the 10 cm intervals. Soil moisture content was measured using the Neutron probe that was calibrated to get the value of volumetric water content. Unsaturated hydraulic conductivity of soil was calculated by using the Libardi Equation. Data were tested using the analysis of variance, the least significant different test (LSD), Duncan Multiple Range Test (DMRT), correlation and regression analysis. The results showed that the hedgerow significantly affected the soil moisture content and unsaturated hydraulic conductivity. Soil moisture content on the hedgerow plots was lower than the control plots. The value of unsaturated hydraulic conductivity in the hedgerow plots was higher than the control plots. Different types of hedgerows affected the soil moisture content and unsaturated hydraulic conductivity. The positive correlation was found between the volumetric soil moisture content and the unsaturated hydraulic conductivity of soil.